Structural and functional changes of cell junctions on effect of ionizing radiation - Somosy, Zoltán (Acta Biologica Szegediensis, 2003)
Cell junctions are specialized regions of the cell membrane that are responsible for the formation of physical connections among the cells. They are also playing a role in cell communication and in the signal transduction processes of the plasma membrane. Following ionizing irradiations, their structural as well as functional changes are clearly detectable. They are generally able to modify the overall cell responses to various agents, whereas in some cases their functional changes can also be brought into relation with some end-points, such as apoptosis or tumor formation. According to experimental data, biologically active molecules (free radicals, signal transfer molecules) formed on the effect of radiation can get across into neighboring cells through the gap junctions that are responsible for intercellular chemical communication, and may there bring about changes characteristic to radiation injury (bystander effect) and they are also involved in/contribute to the so-called radio-adaptation of the cells. The permeability changes in the tight junctions caused by irradiation can be detected by EM and also by biochemical methods. Using morphometric analysis of EM specimens made by freeze-fracture technique, or by immunohistochemical detection of proteins derived specifically from tight junctions, it can be established that there are structural modifications occurring due to irradiation by X-rays. Using tissue culture model systems, radiation induced redistribution of cadherin and ß-catenin, two characteristic structural proteins of adherent junctions, is also detectable. Other molecules are also affected. Their expression or changes could play an important role in the development of acute or delayed injuries, including inflammatory processes occurring in the tissue - either as a cause or as an effect.